ANALISIS PEMBIAYAAN MUDHARABAH, PEMBIAYAAN MUSYARAKAH,PEMBIAYAAN BERMASALAH, LIKUIDITAS, KECUKUPAN MODAL, DAN EFISIENSI BIAYA TERHADAP PROFITABILITAS BANK SYARIAH 2012-2016 - Dewi Yuliana, 14.05.52.0061; Puspitasari, Elen (Students Journal of Accounting and Banking, 2018)
The purpose of this study is to examine and analyze the effects of Mudharabah Financing, Musyarakah Financing, Troubled Financing, Liquidity, Capital Adequacy, and Cost Efficiency to Profitability of Sharia Banks. The type of data used in this study is secondary data, this research data obtained from the financial statements and Annual Report 2012-2016. Sampling method used is Purposive sampling. The amount of data processed by 91 sharia banks. Methods of data analysis using multiple linear regression. The results showed that Mudharabah Financing, Musharaka financing, and Liquidity have no significant negative effect on profitability (ROA), Financing Problems, Capital Adequacy positively influential not significant to profitability (ROA), while at Cost Efficiency significantly negatively affect profitability (ROA). Keywords: Mudharabah Financing, Musharaka Financing, Non-performing Financing, Liquidity, Capital Adequacy and Cost Efficiency.